Fortifying from Radicalism: Campuses' and Students' Efforts in Indonesia and Malaysia - Mochamad Ziaul Haq; Gerardette Philips; R.F. Bhanu Viktorahadi; M. Yusuf Wibisono (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2023)
The development of radicalism has reached all corners of the world, including the Southeast Asian region. The main target for recruiting radicalism movements is young people, especially students. This paper examines the efforts of campus institutions and students in anticipating the influence of radicalism, especially in the campus environment. The study was conducted on students in Indonesia and Malaysia. The method used in this paper is qualitative, through in-depth interviews, focus group discussion (FGD), and document review. This paper finds that students in Indonesia and Malaysia have become aware of the rise of radicalism in their countries, so various responses have been followed to protect themselves from the dangers of this ideology. Efforts undertaken by the campus include a policy of disseminating an understanding of religious or Islamic moderation wasatiyah. Meanwhile, the efforts made by students to fortify themselves include independent efforts through an independent search for knowledge and learning in class, friendship relations, student discussions, and access to social media. All efforts made by campuses and students are part of instrumental actions using campus institutions as bureaucracy. This paper argues that radicalism as a collective action can be anticipated through collective social action, such as by utilizing available instruments.